KUALITAS PAPAN PARTIKEL DARI KOMPOSISI PARTIKEL BATANG KELAPA SAWIT DAN MAHONI DENGAN BERBAGAI VARIASI KADAR PEREKAT PHENOL FORMALDEHIDA - Ahmad Roihan; Rudi Hartono; Tito Sucipto (Program studi Kehutanan USU, 2015)
Oil palm trunk and mahogany’s particle can be used as material particle board. The aim of these study was to evaluated, particle board quality made from compositions of oil palm trunk and mahogany’s particle with several variation of phenol formaldehida adhesive and also to determine the best treatment of this research. Particle board made with size 25 cm x 25 cm x 1 cm. Composition variations particle oil palm trunk and mahogany were 100:0, 75:25, 50:50, 25:75 and the PF adhesive were 8%, 10%, 12%. The results were compared with the SNI 03-2105-2006 standard. This study used using a completely random experimental factorial design with 2 factors and 3 replication. The results showed that of density value was 0.50-0.59 g/cm3, moisture content was 8.43-11.09%, water absorption in immersion for 2 hours was 35.68-58.64%, and 24 hours was 56.01-77.43%. Thickness swelling on immersion for 2 hours was 4.76-10.15%, and 24 hours was 9.73-13.07%, the value of the MOE was 6170-9594 kg/cm², MOR values was 52.37-81.62 kg/cm². Variations of the PF adhesive and composition oil palm trunk and mahogany’s particle doesn’t give the effect of physical and mechanical properties significantly except density. All of MOE and MOR value didn’t fulfill the standards, where as but the density, moisture content value had fulfilled SNI 03-2105-2006 standards. The best treatment in this results was at 75:25 and adhesive 8%. Keywords: oil palm trunk, mahogany’s, phenol formaldehyde, physical and mechanical, particle board.